Peradaban Islam Pada Masa Khalifah Umar Bin Khattab - Putri Nadiyah Elfadhilah; Rani Rani; Anjeli Angreani; Nopsri Handika; Asih Rahmalia; Andri Nopriansyah; Dwi Noviani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Islamic civilization during the time of umar bin khattab, umar bin khattab expanding and spreanding islam outside the arabian peninsula, as well as the policies implemented during his reign. Based on literaly studies from various books on the history of Islamic civilization and the journal history of Islamic civilization, especially books related to caliph umar bin khattab, it is found that islam had a vary rapid growth while umar bin khattab was in office.the results of this study refealed for the first time that the expansion of islam led by umar expanded to only in the arabian peninsula but also spread to various areas such as Damascus, ajnadain, Palestine, Iraq, Persia, Syria, and nahawan. This expansion.is very benesicial for muslims, especially for the development of islam, as well as respect for Islamic law. Second in the policies persued by umar were ijtihad and politics. Ijtihad policy by modifying systems that do not yet exist in the qur’an, as well as improving regulations that need to be revised or modified according to the needs and development of the times. Political policy is to innovate the government structure and state management structure.